Sosialisasi dan Pelatihan Guna Meningkatkan Motivasi Belajar dan Minat Berwirausaha di Lingkungan Pelajar Pada Panti Asuhan Ar-Rahman Medan - Siregar, Alyad Ul; Lubis, Desy Irana Dewi; Isnaini Nur Azhara; Khayru Aqillah; Mhd Rahmad Ramadhan; Pardosi, Wanda (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Community service is the process of implementing knowledge learned in tertiary institutions in order to provide the widest possible benefit to society. One form of service activity is this activity, which aims to foster students' interest in entrepreneurship, which can provide benefits to the community, especially in the environment. Community service activities were carried out at the Ar-Rahman Orphanage in Medan. A series of activities in the form of providing learning motivation, training in entrepreneurship, and providing education in the process of making "Es Lumut" for orphanage children The service at the Ar-Rahman Orphanage has been carried out smoothly, which is marked by the active participation of all parties involved, namely the STIM Sukma Medan campus and the Ar-Rahman Orphanage. Through this service activity, it is hoped that it can help them in entrepreneurship at the orphanage as well as strengthen the sense of brotherhood between educational institutions and social institutions.